Juridical Review On Micro, Small, And Medium Business Loans (MSMEs) With Fiduciary Guarantee In Bank BPD Aceh - Muliana (Journal of Law Science, 2020)
The background of writing this thesis is an interest in the issue of Micro, Small and Medium Enterprise Credit. In writing this thesis, the problem is how to implement micro, small and medium business credit at Bank BPD Aceh, how to provide fiduciary guarantees in micro, small and medium business loans at Bank BPD Aceh, and how to resolve disputes over micro, small and medium business loans. medium that is associated with fiduciary guarantees. based on the title of this thesis, the research is located at Bank BPD Aceh The research method is carried out by data collection, and data collection is carried out by seeking information based on the documents and archives of Bank BPD Aceh related to research, where this aims to find out Micro, Small and Medium Business Credit, namely how to explain the implementation of business credit micro, small and medium enterprises, provision of fiduciary guarantees in micro, small and medium business loans, and dispute resolution of micro, small and medium enterprises credit related to fiduciary guarantees. The results of the study indicate that the settlement of disputes related to fiduciary guarantees can be carried out peacefully, and can be carried out on debtors who have good intentions to settle their credits. Problem solving is carried out by examining in advance the extent to which the goods are tied up through a guarantee institution, so that Bank BPD Aceh can find out its position as a concurrent creditor and the problems it will face in terms of the collateral that has been tied up with other debts it receives as credit collateral. Legal protection in Micro, Small and Medium Business Loans at Bank BPD Aceh with the implementation of the general credit policy (KUP) of Bank BPD Aceh which is the implementation of the Decree of the Board of Directors of Bank Indonesia No. 27/162/KEP/DIR dated March 31, 1995, concerning the obligation to formulate and implement bank credit policies for commercial banks. It was concluded that the micro, small and medium business in the PPK-BM (Guidelines for the Implementation of Small Business Business Credit) is one of the business segments in Bank BPD Aceh which is a banking system implemented by Bank BPD Aceh in carrying out its function as a financial intermediary. for financing micro, small and medium enterprises.